Development of Flipped Classroom Learning Combined with Google Classroom and Video Conference to Improve Students’ Learning Independent and Mathematics Learning Outcomes - Suryawan, I Putu Pasek; Pratiwi, Kadek Ayu Mutiara; Suharta, I Gusti Putu (Journal of Education Technology, 2021)
The problem of this research arises from learning independent is a crucial part needed in learning which then gives certain influence toward learning outcome; hence a right strategy is needed to gain it. This study was developmental study toward flipped classroom learning aiming at: analyzing the validity, practicality and the effectiveness of flipped classroom learning combined with google classroom and video conference. This study was based on ADDIE model. In accordance to the subject of this study, there were three experts in developing learning administrations and two experts in developing learning media in validating stage and 32 students from Junior High School in implementing stage. The results of this research in terms of quantitative findings revealed that the validity of learning administration was worth to be implemented with validity average of lesson plan was around 88,10%, teaching materials was around 90,00%, evaluation instrument was 90,48% and learning media was 90,00 % and those result was categorized into very worth-implementing. The practicality of flipped classroom seen from the questionnaire result showed that students’ respond gained 3,22 which could be categorized into high category, and teachers’ respond was at 3,70 which can be categorized into very high category. In term of learning independent, an improvement was also found, where before learning an average of 2.49 with the low category, and after learning 2.90 with the high category. The result of gain-analysis showed that the gained score reached 0,44 which could be categorized into medium. This result could be categorized into quite effective in improving the students’ math learning outcome. Based  on the result gained during the data analysis, it could be concluded that flipped classroom combined  with google classroom and video conference was effective in improving students’ learning independent and mathematics learning outcomes.